ANALISIS KARAKTERISTIK INDIVIDU DENGAN KELUHAN KELELAHAN KERJA PADA PENGEMUDI TAKSI DI RUNGKUT SURABAYA - Tika Nanda Prastuti; Tri Martiana (Universitas Airlangga, 2017)
Each type of work will cause fatigue. Fatigue is decreasing a person’s condition so that no longerable to perform the work or activities. This study is to find out the relationship between individual characteristics such as age, work period, smoking habits, exercise habits, nutritional status with work fatigue complaints of taxi driver. The method used in this research was observational analytic with cross sectional approach. This study uses a questionnaire tools work fatigue Industrial Fatigue Research Committee (IFRC), weight scales and height or microtoise Stature Meter. The population in this study was a taxi driver in Rungkut Surabaya who work at night time from 14.00 pm–12.00 pm. The studysample of 50 drivers by used purposive sampling method. The results of this study used Chi-Square. Statistical test results indicate that the age of the driver has a low relationship strength, the driver’s working period has a very strong relationship strength, smoking habits driver has a very low relationship strength, exercise habits and nutritional status drivers has a strong relationship. The conclusion that can be drawn from the results of the study there was no association between age, work period, smoking, exercise habits, and nutritional status and work fatigue complaints of taxi drivers. Therefore, need forsocialization or briefing about the dangers of smoking to health, eating vitamin partially substitute for cigarettes and a healthy lifestyle.Keywords: work period, nutritional status, exercise habits, indivudual characteristics, work fatigue complaints, taxi drivers